How Does Procedural Justice Affect Job Crafting? The Role of Organizational Psychological Ownership and High-Performance Work Systems - Zhun Gong; Mengxuan Ren; Yingjie Sun; Ziyi Zhang; Wen Zhou; Xiaowei Chen (Behavioral Sciences)
In today’s highly competitive and complex market environment, enhancing adaptability has become essential for the sustainable development of enterprises. Job crafting, an important strategy for strengthening a company’s core competitiveness, has garnered increasing attention in recent years. However, previous studies have often overlooked its antecedent variables and mechanisms. This study draws on social exchange theory and equity theory to examine how procedural justice influences the cross-level pathways of job crafting. Hierarchical linear modeling (HLM) was employed to analyze data from 76 companies and 1049 employees. The results demonstrate that procedural justice significantly and positively impacts employee job crafting. Additionally, organizational psychological ownership mediates the relationship between procedural justice and job crafting at a cross-level, while high-performance work systems positively moderate the link between organizational psychological ownership and job crafting. These findings reveal a novel pathway for enhancing employee job crafting and offer practical insights for corporate management. Companies should focus on fostering an environment characterized by procedural justice and which promotes organizational psychological ownership to encourage job-crafting behaviors. Moreover, attention should be given to the effectiveness of organizational psychological ownership and to the moderating role of high-performance work systems in this process.